A study on time elements in a textile and clothing supply chain - Hussain, Deedar (2012)
The structure and configuration of the textile and clothing supply chains are changed in many parts of the world in response to the global manufacturing scenario. Significantly, the time based performance of the entities has emerged as a strong competitive option in the higher-end market segments. Based on the new situation, a case study is developed here for measuring the elements of time for the various activities of a supply chain which operates in South Europe. The objective of the study is to identify the business strategy and time based performance of the chain entities.